Hubungan antara Kepercayaan Organisasi dengan Organizational Citizenship Behavior (OCB) Pegawai Pusat Pendidikan dan Pelatihan Bea Dan Cukai Jakarta Timur - Hariyani Priscilia Suherman; Dwi Deswary; Eliana Sari (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This research set aims to discover the relation between organizational trust andorganizational citizenship behavior at Pusat Pendidikan dan Pelatihan Bea dan CukaiEast Jakarta. The research variable is organizational trust as independent variabel (X)and OCB as dependent variable (Y). The method used in this research is a survey method.To collect the data from respondent researcher use an instrument for both variableorganizational trust and OCB.Data analyzing techniques to test the hypothesis using product moment. Beforeusing the product moment researcher has to test the requirement test that cover normalitytest and liniearity test. From the result of hypothesis test for significance correlationresearcher obtain Tscore > Ttable, Tscore = 31,78 and Ttable = 1,995. From the scorewe can conclude that the hypothesis being submitted is accepted and the nil hypothesis isrejected.From the result of the research can be concluded there is a positive relationbetween organizational trust and organizational citizenship behavior of employee atPusat Pendidikan dan Pelatihan Bea dan Cukai East Jakarta. The result also sow thecontribution of organizational trust for OCB is 93,61%. From the score can be describedthat the organizational trust giving a big amount of contribution for the enhancement ofemployee OCB. However to give the positive influence on OCB employee requiredanother factor and not just organizational trust but also another factor that couldincrease the influence of OCB.